Does multifamily therapy help parents of adolescents with anxiety-based school refusal? A qualitative approach - Claire Snegaroff; Maude Ludot-Grégoire; Sara Skandrani; Caroline Barry; Christine Hassler; Salomé Grandclerc; Sevan Minassian; Eloïse Hellier; Rahmeth Radjack; Marie Rose Moro; Aurélie Harf (PLoS ONE, 2025)
Introduction Anxiety-based school refusal is a major public health problem among adolescents, with serious professional, social, and psychiatric consequences in adulthood. Family and especially parental involvement is essential. Multifamily therapy has been shown to be effective in the management of many psychological disorders including anxiety-related disorders. The aim of this qualitative study is to explore the experiences of parents who participated in the MULTI FAST program (a multifamily therapy focused on anxiety-based school refusal). Method Participation in the study was offered to all families who participated in a MULTI FAST group in 2022 and 2023. A semi structured interview was conducted with each parent who agreed to participate, six months after the end of the multi-family therapy. The interviews were analyzed with a qualitative phenomenological method, Interpretative Phenomenological Analysis. Results Thirty-one parents (out of 37, 84%) agreed to take part in the study: 19 mothers and 12 fathers. The mean age for fathers was 51.5 (SD = 6.45) and 48.7 (SD = 4.77) for mothers. Analysis of the interviews revealed four main themes. The first was changes in parents’ representations of their adolescent, with a better understanding of their child’s distress and needs. The second theme was parents looking at themselves in a new light, with less sense of abnormality, less guilt, and looking back at their own relation to school. The third theme was the expression of parental distress to their adolescents, and the fourth described better communication and stronger family groups after the multifamily therapy. Discussion All parents who participated in the study emphasized the help that multifamily therapy had given them. This included an increased sense of parental self-efficacy, better mentalization, and a positive impact on family interactions, with changes in everyone’s place in the family.